Analysis of Employee Work Posture to Reduce Muscle Injury Using the ROSA (Rapid Office Strain Asassment) Method At PT. Sinar Semesta - Rezal Aji Pratama; Eli Mas’idah; Wiwiek Fatmawati (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
Abstract - CV. Sinar Semesta is a manufacturing company that produces various kinds of metal from foundries. In carrying out its production activities PT. Sinar Semesta has several sections such as production and administration. In the process of administrative activities assisted by using a computer as a tool to support work. After observing the company, there were various problems experienced precisely in the administration section, namely the workers often experienced complaints and felt pain in certain parts when doing work. Complaints felt by employees are caused by several factors, one of which is caused by inadequate company facilities so that it affects the work posture of employees. Therefore, it is necessary to analyze the work posture of employees to reduce the risk of muscle injury. In this study, the ROSA (Rapid Office Strain Assessment) method is used to identify the factors that cause muscle pain and to find out the level of risk for employees at PT. Sinar Semesta Klaten and carry out repair analysis to reduce the risk of injury to workers. After processing the data, it was found that the workers at PT. Sinar Semesta has a dangerous level of risk. In addition, suggestions for improvement were obtained to reduce the level of risk, namely by updating the facilities used by workers such as chairs that can be adjusted in height according to employee needs, ergonomic work desks, monitors that can be adjusted in height according to employee needs, mouse and keyboard are distanced and updated with using a wireless system so that it doesn't take up a lot of space, and the need for socialization about the correct application of office ergonomics to employees Keywords: ROSA (Rapid Office Strain Assessment), Risk Level, Work Posture